2019
DOI: 10.1038/s41598-019-43439-5
|View full text |Cite
|
Sign up to set email alerts
|

Stability Mechanism of Two Soybean Protein-Phosphatidylcholine Nanoemulsion Preparation Methods from a Structural Perspective: A Raman Spectroscopy Analysis

Abstract: Ultrasound treatment and high-pressure homogenization were used to prepare soybean protein (SP)-phosphatidylcholine (PC) nanoemulsions in this study. Nanoemulsions prepared by high-pressure homogenization were more stable. The structural changes of SP and PC under ultrasound treatment and high-pressure homogenization treatment were investigated by Raman spectroscopy. It could be concluded that ultrasound and high-pressure homogenization treatments increased both the content of α-helix and unordered structure b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…This could help explain the lack of improvement in survivability during MXSD and FD with WPI-in these more gentle drying technologies, the primary cause of cell death might be membrane oxidation, and as the antioxidant sulfur-rich amino acids lie primarily near the surface in β-Lactoglobulin [32] (the dominant protein in WPI), cleavage or denaturation due to UHPH would not change the ability of those side chains to interact with oxygen species. This might also help explain the differences in WPI and SPI in MXSD and FD, as soy proteins are well known to be low in sulfur-rich amino acids [33][34][35] and the native conformation of soy proteins relies upon disulfide bridges to stabilize the tertiary structure [36].…”
Section: Survivability Of L Plantarum Nrrl B-1927 Powdersmentioning
confidence: 99%
“…This could help explain the lack of improvement in survivability during MXSD and FD with WPI-in these more gentle drying technologies, the primary cause of cell death might be membrane oxidation, and as the antioxidant sulfur-rich amino acids lie primarily near the surface in β-Lactoglobulin [32] (the dominant protein in WPI), cleavage or denaturation due to UHPH would not change the ability of those side chains to interact with oxygen species. This might also help explain the differences in WPI and SPI in MXSD and FD, as soy proteins are well known to be low in sulfur-rich amino acids [33][34][35] and the native conformation of soy proteins relies upon disulfide bridges to stabilize the tertiary structure [36].…”
Section: Survivability Of L Plantarum Nrrl B-1927 Powdersmentioning
confidence: 99%
“…the saturated vs. unsaturated fatty acid content [19,20]. It was recently reported that Raman spectroscopy can also be used to detect structural changes when oils and curcumin [21] or proteins [22] are incorporated into nanodroplets, as well as to study interactions among nanoemulsion components. Textural and rheological investigations were employed as additional techniques to determine the nature of transient liquid crystalline phases and the effect of oil/ water phase variations on the LE-NE formation and stability [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that lecithin energy, as a PL source, is effective in the larval stage by providing inositol, choline for fish growth and increasing the absorption of nutrients (Coutteau et al 1997;Geurden et al 1998). Furthermore, it has been reported that dietary PLs can promote somatic growth by providing energy, increasing the effectiveness of lipid use through emulsification and digestion, increasing lipid transport between organs, and providing phosphatidylcholine with a growthpromoting effect (Kasper and Brown 2003;Geurden et al 1998;Shields et al 2001;Tocher et al 2008;Zhu et al 2019).…”
Section: Discussionmentioning
confidence: 99%